2012
DOI: 10.1002/sce.21018
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis of the relations between opportunities to learn about science and the development of interests related to science

Abstract: Relations between parental reports of children's interests related to science and opportunities for science learning were examined longitudinally in 192 children between ages 4 and 7 years. Science interests were tracked during 1‐year periods (ages 4–5, 5–6, and 6–7) and were more prevalent among boys, particularly prior to age 6 years. Gender differences did emerge in terms of frequencies of opportunities for science learning during all 3 years. Longitudinal path analyses tested relations between children's s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(113 citation statements)
references
References 56 publications
2
101
1
2
Order By: Relevance
“…Alexander et al (2012) discussed how parents supported their children's interest in science by "creating contexts for exploration and learning of science concepts" (p. 782). This type of family support was evident in these students' accounts of their own engagement in science and resonates with the work of Louise Archer's group (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alexander et al (2012) discussed how parents supported their children's interest in science by "creating contexts for exploration and learning of science concepts" (p. 782). This type of family support was evident in these students' accounts of their own engagement in science and resonates with the work of Louise Archer's group (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding such complexity, gender-related gaps tending to favour males continue to be evident, particularly in physical science and mathematics. Our analysis of the research, however, revealed few studies that interrogated female students directly or deeply about the array of influences that seem to underpin their choices about studying science at secondary school, although many have suggested that this work be undertaken (Alexander et al 2012;Gill & Bell 2013;Homer et al 2014;Wang 2013). To contribute to addressing that apparent deficit in the literature, yet grounded in the assortment of findings and potential explanations from previous research, this study directly asked female students currently enrolled in upper secondary school physics, about strong influences important to their own science education experiences, including current interests and future aspirations.…”
Section: Introductionmentioning
confidence: 99%
“…The Elementary/Secondary Transition and Other Short Transitions Alexander et al (2012) had already noticed that very young children (especially boys) transitioning into school and immediately thereafter tended to have a decline in interest.…”
Section: Boy-girl Differencesmentioning
confidence: 99%
“…To measure children's interest in science Alexander and her colleagues documented parents' reports of the activities their children engaged in (Alexander, Johnson, & Kelly, 2012 ). To measure children's interest in science Alexander and her colleagues documented parents' reports of the activities their children engaged in (Alexander, Johnson, & Kelly, 2012 ).…”
Section: Declines In Science Motivation and Misunderstanding The Natumentioning
confidence: 99%